Deep Promotion Strategic Planning Analysis Competition for Students - Sindhu Alamsyah; Agus Rahayu; Puspo Dewi Dirgantari (Dinasti International Journal of Education Management And Social Science, 2023)
SMK IT daarul Abror really understands that marketing strategy is very important, especially in terms of competition between SMA/SMK equivalent in getting students. This study aims to develop strategic promotion planning formulations in competition to get students, so that data collection is carried out through interviews, observation, and document studies. internal and external environmental analysis at SMK IT Daarul Abor which is used to formulate promotion strategic planning in getting students.